2013
DOI: 10.1093/cid/cit735
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of IL-23 in a Subset of Patients With Post-Lyme Disease Symptoms Following Erythema Migrans

Abstract: High TH1-associated responses correlated with more effective immune-mediated spirochetal killing, whereas high TH17-associated immune responses, often accompanied by autoantibodies, correlated with post-Lyme symptoms, providing a new paradigm for the study of postinfectious symptoms in a subset of patients with Lyme disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 29 publications
6
84
0
Order By: Relevance
“…These symptoms might be a part of a central sensitization syndrome 179 or be attributable to immune system abnormalities, for example, increased levels of IL-23 (REF. 180) or heightened levels of anti-neuronal antibodies 181 . This area is further confused as PTLDS, or what has been referred to as ‘chronic Lyme disease’, has become a diagnosis for medically unexplained symptoms, even when patients have no evidence of past or present Lyme borreliosis 182,183 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…These symptoms might be a part of a central sensitization syndrome 179 or be attributable to immune system abnormalities, for example, increased levels of IL-23 (REF. 180) or heightened levels of anti-neuronal antibodies 181 . This area is further confused as PTLDS, or what has been referred to as ‘chronic Lyme disease’, has become a diagnosis for medically unexplained symptoms, even when patients have no evidence of past or present Lyme borreliosis 182,183 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…In our experiments, both cytokines were present to induce the development of IL-17. Apparently, the presence of IL-23 is important for promoting the development of Th17 cells, but IL-1b was the key driver of the amount of IL-17 produced A previous study by Strle et al [28] showed elevated levels of IL-23 in patients with post-Lyme disease symptoms, and elevated levels of IL-17 have been found in cerebrospinal fluid of patients with neuroborreliosis [23]. It has been suggested that Th17 cells and their associated cytokines are involved in the pathogenesis of Lyme arthritis [11,29,30].…”
Section: Discussionmentioning
confidence: 94%
“…33 Some have suggested that patients with elevated interleukin 23 during infection may be more likely to have persistent symptoms after treatment. 34 Other work suggests that active infection results in elevated serum concentrations of CXCL9 and CXCL10. 35 The implications, or even the reproducibility, of these observations remain to be determined.…”
Section: Lyme Pathophysiologymentioning
confidence: 99%